EVALUATION OF INPATIENT SERVICES AT H. ANDI SULTHAN DAENG RADJA REGIONAL GENERAL HOSPITAL BULUKUMBA REGENCY - Sulmiah, Sulmiah; Fajar, Rahmat; Guntur, Muhammad; Pratiwi Johansyah, Oky Nur (Universitas Negeri Makassar, 2024)
This study aims to determine the Quality of Inpatient Services at the H. Andi Sulthan Daeng Radja Regional General Hospital, Bulukumba Regency, this study uses a qualitative approach. Data collection was carried out through observation, interview, and documentation techniques. The Data Analysis Technique used in this study is interactive data analysis through the following stages: data condensation, data presentation, and conclusion testing.The results of this study show that the Inpatient Services at the H. Andi Sulthan Daeng Radja Regional General Hospital, Bulukumba Regency have generally run well, although there are still shortcomings in its implementation. This can be seen from several indicators, namely, determination, implementation and responsibility. However, there are still shortcomings in administrative personnel who are still not agile in serving non-medical patients, but the Bulukumba Regency Government has made every effort to improve services at the H. Andi Sulthan Daeng Radja Regional General Hospital, Bulukumba Regency, including inpatient services. The supporting factor in inpatient services at H.Andi Sulthan Daeng Radja Bulukumba Hospital is the existence of good communication between medical personnel and patients, and also receives support from the government and the local community. The inhibiting factor in the service at H. Andi Sulthan Daeng Radja Hospital, Bulukumba Regency is in the research licensing section which is still charged to get a permit for research.